2011
DOI: 10.1093/arclin/acr082
|View full text |Cite
|
Sign up to set email alerts
|

Does the Iowa Gambling Task Measure Executive Function?

Abstract: The Iowa Gambling Task (IGT) is assumed to measure executive functioning, but this has not been empirically tested by means of both convergent and discriminant validity. We used structural equation modeling (SEM) to test whether the IGT is an executive function (EF) task (convergent validity) and whether it is not related to other neuropsychological domains (discriminant validity). Healthy community-dwelling participants (N = 214) completed a comprehensive neuropsychological battery. We analyzed the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 36 publications
4
41
0
3
Order By: Relevance
“…This would be consistent with observations of unimpaired neurocognitive performance in PB-samples of previous studies (Black et al, 2012;Voth et al, 2014). Furthermore, within the current study, we revealed some correlations between decision-making performance and the neuropsychological tasks as well as intelligence, which were partly consistent with previous studies (Brand et al, 2008;Gansler et al, 2011;Schiebener et al, 2011;Webb et al, 2014). However, the validity of the correlations is limited due to small sample sizes.…”
Section: Discussionsupporting
confidence: 93%
“…This would be consistent with observations of unimpaired neurocognitive performance in PB-samples of previous studies (Black et al, 2012;Voth et al, 2014). Furthermore, within the current study, we revealed some correlations between decision-making performance and the neuropsychological tasks as well as intelligence, which were partly consistent with previous studies (Brand et al, 2008;Gansler et al, 2011;Schiebener et al, 2011;Webb et al, 2014). However, the validity of the correlations is limited due to small sample sizes.…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, this research suggests that latter trials, particularly after trial 40, provide a better index of adaptive decision making. In support of this, one study found that better criterion and construct validity were achieved when the last 60 trials of the IGT were used (Gansler, Jerram, Vannorsdall, & Schretlen, 2011). We therefore disregarded the first 40 acquisition trials and evaluated the number of choices from advantageous decks during the last 60 trials.…”
Section: Methodsmentioning
confidence: 88%
“…Thus, participants must discriminate between short-term and long-term consequences. The Gambling Task has been used in a variety of populations, including the HIV population 5,8 and has demonstrated convergent validity with attention and executive functions 31 and ecological validity among drug-abusers. 32 To examine whether participants were able to learn to discriminate between short-term and long-term consequences, a learning index was created by subtracting the average number of advantageous cards (i.e., decks A and B) selected from the first two blocks of 20 cards from the average of advantageous cards for the last three blocks.…”
Section: Methodsmentioning
confidence: 99%